Handbook of VLSI microlithography : principles, technology, and applications - Helbert, John N. (Materials science and process technology series. Electronic materials and process technology., 2001)
This handbook gives readers a look at the technology of printing very high resolution and high density integrated circuit (IC) patterns into thin resist process transfer coatings - including optical lithography, electron beam, ion beam, and X-ray lithography. The book's main theme is the special printing process needed to achieve volume high density IC chip production, especially in the Dynamic Random Access Memory (DRAM) industry. The book leads off with a comparison of various lithography methods, covering the three major patterning parameters of line/space, resolution, line edge, and pattern feature dimension control. The book's explanation of resist and resist process equipment technology describes the relationship between the resist process and equipment parameters. The basics of resist technology are also covered - including an entire chapter on resist process defectivity and the potential yield limiting effect on device production.